PRODUCTION AND CHARACTERIZATION OF A FERMENTED BEVERAGE FROM PINEAPPLE (Ananas comosus) PEELS - Ferreira, Loren Gomes; Okura, Mônica Hitomi; Zambrano, Francy (Seven Editora, 2026)
The objective of this work was to evaluate the use of pineapple peels in the production of a fermented beverage, contributing to the valorization of agro-industrial waste and the development of more sustainable food products. During fermentation, pH and °Brix analyses were performed at 12-hour intervals. The fermented beverage was analyzed for lactic acid bacteria counts and determination of coliforms at 35°C and 45°C, Salmonella, anaerobic mesophilic bacteria, and molds and yeasts. A sensory acceptance test and purchase intention assessment of the fermented beverage made with pineapple peels were conducted in comparison with a commercial fermented beverage. The results for sensory evaluation, and purchase intention of the two samples were subjected to analysis of variance (ANOVA) and Tukey's test at a 5% significance level. Fermentation time did not cause a significant difference (p